Successful ICSI in Mice Using Caput Epididymal Spermatozoa - Fernández-González, Raúl; Laguna, Ricardo; Ramos-Ibeas, Priscila; Pericuesta, Eva; Alcalde-Lopez, Víctor; Perez-Cerezales, Serafín; Gutierrez-Adan, Alfonso (Frontiers in Cell and Developmental Biology, 2019)
Spermatozoa undergo their last phase of spermiogenesis, known as maturation, as they pass through the epididymis. A recent report indicates that mouse immature spermatozoa retrieved from the caput epididymis for intracytoplasmic sperm injection (ICSI) give rise to embryos with multiple developmental defects. Further, these embryos were unable to develop to term after their transfer to surrogate mothers. Herein, we examined the potential of mouse caput spermatozoa to produce normal embryos by comparing the use of caput vs cauda epididymal spermatozoa for in vitro fertilization (IVF) or ICSI. Two methods for the separation of sperm heads prior to ICSI were also compared: freezing/thawing or drawing through a syringe. We found that in contrast to caudal spermatozoa, caput spermatozoa failed to produce embryos via IVF, confirming their immature state. However, regardless of the method employed for the separation of sperm heads, similar efficiencies of blastocyst production in vitro and development to term after transfer to surrogate mothers were observed following ICSI using both caput and cauda epididymal spermatozoa. It therefore seems that mice spermatozoa recovered from the caput epididymis are as valid as caudal spermatozoa for the production of embryos and offspring by ICSI.